U-shape and Cluster Seating Arrangement in Teaching English as Foreign Language in Yayasan Dana Punia - Pranena, I Made Widwan (Journal of Educational Study, 2022)
The current problem focused on seating arrangement. The data were collected through observation, video recording, and interview. Data were analyzed by using Interactive Data Analysis. After the observation done, there were differences on students’ responses in U-shape and Cluster seating arrangements. When U-shape seating arrangement implemented, the students become hesitated in participating in the classroom activities. Meanwhile Cluster seating arrangement promoted more students’ participations. It was suggested to decide what types of response the teacher want their students give to the lesson before implementing those seating arrangements.